(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article describes similes in two stages. At the language level, the structural and compositional pattern of the simile as a model is characterized; at the speech level, views are presented on the study of the pragmatic meaning of the simile in relation to the communicative situation.